An improved extraction chromatographic purification of tungsten from a silicate matrix for high precision isotopic measurements using MC-ICPMS. Issue 4 (28th February 2018) - Mei, Qing-Feng; Yang, Jin-Hui; Yang, Yue-Heng
Abstract : An improved chemical method is developed to accurately measure the W isotopic compositions of silicate samples with a precision of better than ±0.05 ε on ε 182 W. Abstract : An improved chemical method is developed to accurately measure the W isotopic compositions of silicate samples with a precision of better than ±0.05 ε on ε 182 W. Compared with the conventional method, two developments of this method mainly include the sample digestion process that is modified to better W dissolution from the co-precipitations and the W separation procedure. The optimized extraction chromatography using TEVA resin is designed to more efficiently separate W from Ti, Zr and Hf after the first-stage cation-exchange procedure with the percent recovery of W more than 85%. The blank during the whole procedure is less than 0.3 ng and is negligible for W isotopic analysis. The W isotopic ratios of Alfa Aesar W standard solution and a variety of silicate reference materials, i.e., RGM-2, GSP-2, AGV-2, JB-3, BCR-2 and BHVO-2, are measured by multi-collector inductively coupled plasma mass spectrometry (MC-ICP-MS). RGM-2, GSP-2, AGV-2, JB-3 and BCR-2 have normal ε 182 W values, identical to that of the terrestrial Alfa Aesar W standard, whereas BHVO-2 has a negative ε 182 W value of −0.09 ± 0.05 (2SD, N = 10). The duplicate measurements of Alfa Aesar W standard solution RGM-2 and BHVO-2 show that the external reproducibility of ε 182 W is usually better than 5 ppm (2SD), which is the most precise among the published data measured by MC-ICPMS and can be comparable to the precision acquired by negative thermal ionization mass spectrometry (N-TIMS) (about 5 ppm). All these results show that our new method provides an efficient way to precisely measure W isotopic compositions of silicate materials. It provides a widely useful tool to reveal the earliest history of the silicate earth and offers the ability to resolve sub-million-year age differences in meteorites.